2014
DOI: 10.1103/physrevlett.113.116801
|View full text |Cite
|
Sign up to set email alerts
|

Braiding Non-Abelian Quasiholes in Fractional Quantum Hall States

Abstract: Quasiholes in certain fractional quantum Hall states are promising candidates for the experimental realization of non-Abelian anyons. They are assumed to be localized excitations, and to display non-Abelian statistics when sufficiently separated, but these properties have not been explicitly demonstrated except for the Moore-Read state. In this work, we apply the newly developed matrix product state technique to examine these exotic excitations. For the Moore-Read and the Z3 ReadRezayi states, we estimate the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
51
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 64 publications
2
51
0
Order By: Relevance
“…They identified a large class of model WFs and their quasihole excitations with Conformal Field Theory (CFT) correlators from which the topological content of the phase may be read off (under the generalized screening assumption [58]). It furthermore allows for an exact Matrix Product State (MPS) description of these strongly correlated phases of matter [59][60][61], allowing for large scale numerical study of their relevance and properties [62,63].…”
mentioning
confidence: 99%
“…They identified a large class of model WFs and their quasihole excitations with Conformal Field Theory (CFT) correlators from which the topological content of the phase may be read off (under the generalized screening assumption [58]). It furthermore allows for an exact Matrix Product State (MPS) description of these strongly correlated phases of matter [59][60][61], allowing for large scale numerical study of their relevance and properties [62,63].…”
mentioning
confidence: 99%
“…We consider the master formula for the case m 1 = 4, Eq. (20), since it yields all braid matrices. The master formula is:…”
Section: Wave Functions For General Mmentioning
confidence: 99%
“…In the last years, there has been significant progress for explicitly computing braiding properties of various types of quasiholes [14][15][16][17][18][19][20], but the quasielectrons are again more complicated to work with. For the latter it has been found that the braiding properties are as expected for the composite fermion version of the Laughlin quasielectrons [21,22], while for Laughlinʼs proposal for the quasielectron wavefunction the expected braiding statistics is obtained in the thermodynamic limit when considering a finite size braiding loop [23,24].…”
Section: Introductionmentioning
confidence: 99%